OPTIMASI TATA LETAK STASIUN KERJA DAN PENINGKATAN KINERJA OPERATOR MELALUI ERGONOMI DIGITAL DAN DESAIN BERBASIS SIMULASI DALAM LINGKUNGAN INDUSTRY 4.0 - Ade Suhara; Ade Astuti Widi Rahayu; Afif Hakim; Nana Rahdiana; Mayasari, Nanny (LPSDI Bina Patria, 2025)
This study explores the integration of digital ergonomics and simulation-based design to optimize workstation layout and enhance operator performance in Industry 4.0 environments. A mixed-method approach was employed, combining digital time study, ergonomic risk assessments, and virtual simulation modeling to evaluate and improve work processes. The research found that ergonomic redesigns, supported by digital twin technology, resulted in significant improvements in both operator comfort and task efficiency, with a 16.6% reduction in cycle time and a 16% increase in work efficiency. RULA scores were reduced from 6 to 3, indicating a significant decrease in ergonomic risk. This study demonstrates the potential of predictive ergonomics and user-centered design in optimizing workplace safety and productivity within the context of modern manufacturing systems. The findings contribute to data-driven design methodologies that can be applied to a variety of industrial settings.